(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pre diabetes is a state where the glycaemic parameters above normal but below diabetes thresholds. Nearly 70% of Prediabetic adults are prone for Diabetics and associated with increased risk of diabetes, cardiovascular events, and mortality. Lifestyle changes are the first line treatment. Objectives: 1. To assess the risk of Type 2 diabetes mellitus and Pre-diabetes of the participants by using Indian diabetic risk score. 2. To determine the association between identified risk factors and the presence of risk diabetes among study participants. Materials and Methods: A Community based Cross –sectional study was conducted for two months among 351 participants of aged 30 years and above 30 years, who were not a known diabetics and residing in the field practice area of Chandragiri. Indian Diabetes Risk Score is a tool used to classify risk group. Ethical clearance was obtained from the Institutional Ethical Committee and informed consent was taken from the participant. Collected data was coded and entered into a Microsoft excel and analyzed using statistical package for the social sciences (SPSS) software version 26. Results: Among 351 participants 50.4% of the study subjects were in moderate risk followed by 38.2% were in high risk while 11.4% were in low risk according to IDRS. Among study participants, 20% had a family history of Diabetes mellitus, 25% were diagnosed with Pre -diabetics, 4% were newly diagnosed as diabetics. Family history, larger waist circumference and lack of physical activity were found to be significantly associated with risk of diabetes. Conclusions: Among 351 patients, nearly one fourth were identified as Pre diabetics and 4% as diabetics. Current study revealed that the early identification of high-risk individuals and planning for appropriate measures to delay the onset of pre-diabetes and diabetes, so that we can reduce the burden of diabetes in India.